2019
DOI: 10.1038/s41467-019-12378-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface-kinetics mediated mesoporous multipods for enhanced bacterial adhesion and inhibition

Abstract: Despite the importance of nanoparticle’s multipods topology in multivalent-interactions enhanced nano-bio interactions, the precise manipulation of multipods surface topological structures is still a great challenge. Herein, the surface-kinetics mediated multi-site nucleation strategy is demonstrated for the fabrication of mesoporous multipods with precisely tunable surface topological structures. Tribulus-like tetra-pods Fe3O4@SiO2@RF&PMOs (RF = resorcinol-formaldehyde resin, PMO = periodic mesoporous org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 50 publications
0
64
0
Order By: Relevance
“…At the same time, the use of AIEgens endows the bioimaging experiments with wash-free characteristics on account of the nonluminescent behavior of single-molecule species. AIEgens also have other favorable characteristics such as high photostabilities and large Stokes shifts (the difference between maximum absorption and emission wavelength), which had led to them being widely used in life sciences, optical electronics, and as chemoprobes or bioprobes, etc [29][30][31][32][33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the use of AIEgens endows the bioimaging experiments with wash-free characteristics on account of the nonluminescent behavior of single-molecule species. AIEgens also have other favorable characteristics such as high photostabilities and large Stokes shifts (the difference between maximum absorption and emission wavelength), which had led to them being widely used in life sciences, optical electronics, and as chemoprobes or bioprobes, etc [29][30][31][32][33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…An active bacteria-targeting nanocapturer with controlled release of antibiotics in particular not only reduces the toxicity of antibiotics but also improves therapeutic effects for bacterial infections 9 . This bacteria-targeting capability can also be achieved by promoting interaction between nanoagents and bacteria via their chemical components on the surface (e.g., proteins, peptidoglycan, and lipopolysaccharides) 25 , 26 . It has been reported that physical forces such as magnetic fields can deliver drug-loaded nanoplatform to infection sites with high specificity and efficiency 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid materials especially nanostructures with high complexity have attracted intensive attention due to their elegant structures and elaborate functionalities 1 4 . The nanostructural complexity can be classified according to (1) composition (e.g., conjugating different components) 5 , 6 , (2) architecture (e.g., manipulating geometric arrangements) 7 9 , and (3) the integration of both compositional and architectural diversity into one nanostructrure 10 12 . As an important family of porous crystalline materials, the composition and architecture of metal-organic frameworks (MOFs) are both key factors for their properties and applications 13 19 .…”
Section: Introductionmentioning
confidence: 99%